POSITIVE AND NEGATIVE IMPACT OF PLACEMENT OF NON-PROMOTIONAL PRODUCTS AROUND PROMOTED PRODUCTS: ANALYSIS OF HOW PRODUCT PLACEMENT INFLUENCES CONSUMER ENGAGEMENT AND BRAND LOYALTY - Raden Roro Fatmasari; Anggun Yolistina; Nida Garnida Fitrianti (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Non-promotional product placement plays an important role in modern marketing strategy, influencing consumer engagement and brand loyalty. In this context, this research explores various factors that influence the relationship between consumers and brands promoted through non-promotional product placement. Based on the analysis of related literature, factors such as product relevance to the brand, store environment, product category, and consumer preferences have a significant impact on consumer engagement and brand loyalty. Product placement that is relevant to the brand, placed in a pleasant store environment, in high-involvement product categories, and in line with brand-aligned consumer preferences tends to increase consumer engagement and brand loyalty. Conversely, inappropriate product placement, a chaotic store environment, low-involvement product categories, and a mismatch between consumer and brand preferences can damage the relationship between consumers and brands. Therefore, companies need to pay close attention to their product placement strategies, ensuring that products are positioned appropriately according to the brand, a pleasant store environment for consumers, and product categories that allow for high engagement. Additionally, a good understanding of consumer preferences and values is also important to ensure that product placement supports, rather than undermines, the relationship between consumer and brand.